PENGALAMAN WISATAWAN MENGIKUTI COOKING CLASS DAN ANALISIS SWOT DI BALI FARM COOKING SCHOOL - Bagus Ketut Soma Antara, Ida; Septiyani, Sania; Ayu Eka Suwintari, I Gusti; Ayu Melistyari Dewi, I Gusti (CV. Lafadz Jaya, 2024)
This research explores the experiences of tourists participating in cooking classes at the Bali Farm Cooking School. The data analyzed are tourist comments on TripAdvisor regarding